A Cognitive Profile of Obesity and Its Translation into New Interventions - Jansen, Anita; Houben, Katrijn; Roefs, Anne (Frontiers in Psychology, 2015)
Change your lifestyle: decrease your energy intake and increase your energy expenditure, is what obesity experts tell people who need to lose weight. Though the advice might be correct, it appears to be extremely difficult to change one’s lifestyle. Unhealthy habits usually are ingrained and hard to change, especially for people with an ‘obese cognitive profile’. Knowledge of the cognitive mechanisms that maintain unhealthy eating habits is necessary for the development of interventions that can change behavior effectively. This paper discusses some cognitive processes that might maintain unhealthy eating habits and make healthier eating difficult, like increased food cue reactivity, weak executive skills and attention bias. An effort is also done to translate these basic scientific findings into new interventions which aim to tackle the sabotaging cognitive processes. Preliminary studies into the effectiveness of these interventions, if available, are presented.